Ant Community (Hymenoptera: Formicidae) from Four Ecosystems Site in Bungku Village, Jambi Province KOMUNITAS SEMUT (HYMENOPTERA: FORMICIDAE) PADA EMPAT TIPE EKOSISTEM YANG BERBEDA DI DESA BUNGKU PROVINSI JAMBI - Noor Farikhah Haneda; Nisfi Yuniar (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Deforestation or transformation of forest function to non-forest has been playing a role in the changes of ecosystem and species in it. Insect as one of the living fauna that live in the forest is an interesting aspect to be studied, especially ants. This experiment was conducted in Bungku, Bajubang District, Batanghari Regency, Jambi. Sampling technique using pitfall traps in four ecosystem. The four ecosystem mentioned is secondary forest, oil palm plantations, rubber plantations, and jungle rubber. The results found there were 5 484 individuals of 50 ant morphospecies, 33 genera of 6 subfamily i.e. Formicinae, Myrmicinae, Ponerinae, Dolichodorinae, Pseudomyrmicinae, and Dolichorinae. Secondary forest is an ecosystem that relatively stable with the value of diversity index H '= 2.76, index of richness DMg = 4.96, and index of evenness E = 0.70. The ant communities depend on environment factor of each ecosystem.Keywords: Ant communities, jungle rubber, oil palm plantation, rubber plantation, secondary forest